Occurrence of plasmids in Danish isolates of Vibrio anguillarum serovars O1 and O2 and association of plasmids with phenotypic characteristics. - Larsen, J L (1991)
Two hundred and twenty-eight isolates of Vibrio anguillarum serovar O1 (125 isolates) and serovar O2 (103 isolates) have been characterized with regard to plasmid contents, biochemical properties, and in vitro hemagglutination and hydrophobic properties. Among 74 V. anguillarum isolates from diseased fish, 63 carried only a 67-kb plasmid (pJM1), 9 carried an additional 98-kb plasmid, and 1 isolate carried only the 98-kb plasmid. Only one isolate was without plasmids. In V. anguillarum serovar O1 from nondiseased fish (mucus and gills), plasmids of the same sizes were present in 29 isolates (58%), whereas 21 isolates (42%) were plasmid free. Based on hemagglutination and biochemical properties, V. anguillarum serovar O1 isolates were divided into eight biovars. The plasmid-carrying strains (102 isolates) all fell within biovars 1 and 2, whereas the 23 strains of biovars 3 to 8 were without plasmids. It was tentatively concluded there are two populations of V. anguillarum serovar O1. One population contains plasmid(s), is hemagglutination negative and trehalose negative, and does not form pellicles in broth cultures, whereas the other population is plasmid free and has the opposite characteristics. The former group is the one related to disease in fish. All 20 V. anguillarum serovar O2 isolates from the environment were without plasmids, whereas 54 (65%) of the isolates from fish (trout and cod) carried plasmids. The biochemical diversity within serovar O2 was pronounced; 13 different biovars were demonstrated. No correlation between the presence of plasmids and biochemical properties was observed.